The Influence of Gender, Body Mass Index, Work Fatigue and Noise Exposure on Blood Pressure among Manufacturing Industry Workers - Nurvita Eka Rizky; Bhisma Murti; Sumardiyono; Setyo Sri Rahardjo; Revi Gama Hatta Novika (Journal of Epidemiology and Public Health, 2025)
Background: Noise in the work environment can exceed a set threshold and have an impact on workers' health, including increased blood pressure. In addition to noise, other factors such as work fatigue, body mass index, and gender also contribute to the risk of hypertension. Preliminary studies show that exposure to high noise and manual work activities is at risk of causing fatigue, so it requires further analysis of the influence of these factors on the blood pressure of industrial workers. Subjects and Method: The study design was a cross-sectional study. The study was conducted in Karanganyar Regency, Central Java in February-April 2025. Sampling in this study was conducted using the Fixed Exposure Sampling method, involving 200 worker samples from a herbal medicine factory and a fireworks factory in Karanganyar Regency, Central Java. The method used to collect data in this study was analytical observations with a cross-sectional approach. The analysis used in this study was path analysis. The dependent variable was blood pressure. The independent variables were noise exposure, fatigue, body mass index, and gender. Results: Blood pressure increased with high fatigue (b= 0.15; 95% CI <0.01 to 0.29; p= 0.038), noise exposure (b= 0.15; 95% CI= 0.02 to 0.28; p= 0.020). Blood pressure in female workers was lower than in men (b= -0.14; 95% CI= -0.28 to -0.01; p= 0.034). Blood pressure was indirectly affected by body mass index. Conclusion: This study shows that noise exposure and work fatigue have a direct effect on increasing blood pressure; women have lower blood pressure than men, while body mass index has an indirect effect on increasing the blood pressure of workers.